Tempos de resistência e de inovação : a arquitectura militar portuguesa no reinado de D. Manuel I (1495-1521) - Barroca, Mário Jorge (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The author describes the evolution of Portuguese military architecture in the course of the reign of King Manuel I (1495-1521), during the so-called "transition period" when late medieval castles were adapted to receive artillery. Two phases are defined. The first until 1508-10, when castles received small improvements so as to be able to use the new weapons. In the second phase, after 1510, castles received more radical changes mainly due to the work of two architects - Diogo de Arruda and Francisco de Arruda - who had also the experience of building the tower of Belém, the new castle of Évora, the castle of Vila Viçosa and the tower of the castle of Évora Monte. The author emphasises the close similarity of the castles of Vila Viçosa and Steinvikholm (Norway).